2020
DOI: 10.3390/jcm9103207
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia: An Aggravating Factor in Asthma

Abstract: Asthma is a common chronic respiratory disorder with relatively good outcomes in the majority of patients with appropriate maintenance therapy. However, in a small minority, patients can experience severe asthma with respiratory failure and hypercapnia, necessitating intensive care unit admission. Hypercapnia occurs due to alveolar hypoventilation and insufficient removal of carbon dioxide (CO2) from the blood. Although mild hypercapnia is generally well tolerated in patients with asthma, there is accumulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 133 publications
(244 reference statements)
0
7
0
Order By: Relevance
“…One study of total hip replacements found that chronic obstructive pulmonary disease (COPD) increased 90- day mortality, mortality at one year, infections within the first year post-operatively, and 30-day readmissions [ 13 ]. Asthma is another common chronic respiratory comorbidity that may lead to alveolar hypoventilation and hypercapnia, potentially resulting in poor lung, skeletal muscle, and innate immune system function [ 14 ]. Furthermore, chronic steroid use, which is often used to treat severe asthma, has been shown to impair wound healing and could potentially increase wound complications [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study of total hip replacements found that chronic obstructive pulmonary disease (COPD) increased 90- day mortality, mortality at one year, infections within the first year post-operatively, and 30-day readmissions [ 13 ]. Asthma is another common chronic respiratory comorbidity that may lead to alveolar hypoventilation and hypercapnia, potentially resulting in poor lung, skeletal muscle, and innate immune system function [ 14 ]. Furthermore, chronic steroid use, which is often used to treat severe asthma, has been shown to impair wound healing and could potentially increase wound complications [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercapnia [HP:0012416], i.e. an elevated level of CO 2 in the blood could be related to the effects of asthma on respiration 30 ; and Increased hematocrit [HP:0001899] could be related to chronic hypoxia, although our analysis does not allow any conclusions about the pathomechanisms of observed laboratory abnormalities. .…”
Section: Screen For Biomarkers Correlated With Progression Into Sever...mentioning
confidence: 99%
“…It is increasingly evident, that various non-excitable cells, such as alveolar epithelial cells, fibroblasts and immune cells are sensitive to the changes in CO 2 concentrations independently of intra-and extracellular pH, reactive oxygen species (ROS) and involvement of the carbonic anhydrases (Putnam et al, 2004;Shigemura et al, 2017;Cummins et al, 2019). In contrast to earlier reports, which suggested that hypercapnia might be tolerated or even beneficial in the setting of critically ill patients (Fuller et al, 2017;Roberts et al, 2018); more recent studies have shown that elevated CO 2 levels are associated with higher complication rates, increased risk of exacerbations, more severe disease states, worse outcomes and an increased risk of mortality both for acute and chronic lung diseases (Yang et al, 2015;Nin et al, 2017;Husain-Syed et al, 2020;Shigemura et al, 2020). In addition, translational studies established that high CO 2 levels impair alveolar fluid clearance, innate immunity and cellular host defense, decrease cytokine production, downregulate phagocytosis and macrophage activity.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, ER stress plays a pivotal role in the pathomechanism of various respiratory diseases, including but not limited to COPD (and in particular cigarette smoke exposure), viral and bacterial pneumonia, asthma, interstitial lung diseases and cystic fibrosis (Korfei et al, 2008;Lawson et al, 2011;Kenche et al, 2013;Kim et al, 2013;van 't Wout et al, 2015;Lee et al, 2016;Marciniak, 2017;Tang et al, 2017;Schmoldt et al, 2019), many of which are accompanied by hypercapnia (Vadasz et al, 2012b;Shigemura et al, 2020). Notably, these disease states also often lead to hypoxia.…”
Section: Introductionmentioning
confidence: 99%